1996
DOI: 10.1152/ajpheart.1996.271.4.h1333
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral analysis for autonomic influences in heart rate and blood pressure variability in fetal lambs

Abstract: Variability of R-R intervals and arterial blood pressure signals in chronically instrumented fetal lambs was analyzed by power spectral analysis based on an assumption of maximum entropy. There were four consistent components, very low (VL, 0.01-0.025 cycle/beat), low (L, 0.025-0.125 cycle/beat), middle (M, 0.125-0.2 cycle/beat), and high (H, 0.2-0.5 cycle/beat), in the normal heart rate variability and blood pressure spectra. Integrated peaks in the power spectrum were compared before and after the administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 0 publications
4
44
0
Order By: Relevance
“…Power within the L frequency range was increased significantly in the nimesulide-treated fetuses. Power in the low-frequency range is influenced both by sympathetic and parasympathetic activity, although previous experiments by Kimura et al (20), suggest that beta-adrenergic blockade in the fetal sheep had a greater influence on L power than did cholinergic blockade (20). In that study, beta blockade reduced L power 78%, while cholinergic blockade reduced power in this frequency range 61% (20).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Power within the L frequency range was increased significantly in the nimesulide-treated fetuses. Power in the low-frequency range is influenced both by sympathetic and parasympathetic activity, although previous experiments by Kimura et al (20), suggest that beta-adrenergic blockade in the fetal sheep had a greater influence on L power than did cholinergic blockade (20). In that study, beta blockade reduced L power 78%, while cholinergic blockade reduced power in this frequency range 61% (20).…”
Section: Discussionmentioning
confidence: 62%
“…In 7 control and in 5 nimesulide-treated fetuses, we quantified the power spectra of the variations in fetal heart rate, using methods similar to that reported by Kimura and coworkers (20) and later supported by studies by Li and coworkers (21). Five-minute epochs of fetal femoral or lingual arterial blood pressure, sampled at a rate of 60 Hz at the time of experimentation, were analyzed for heart period using LabView ver.…”
Section: Methodsmentioning
confidence: 99%
“…Using a 64-ch MCG, Fukushima, et al found that the activity of the sympathetic and parasympathetic nervous systems, as evaluated from the LF/HF ratio, were enhanced at gestational ages of 32 weeks and later, 13) consistent with previous reports of a conversion point at 32 weeks of gestation. 22,23) We found that the ANS activity, as evaluated by the CV and LF/ HF ratio using SAVP-ECG, was remarkably enhanced just after birth. Akselrod, et al discovered characteristic 0.1-Hz and 0.3-Hz frequency band levels (spectral peaks) in a spectral analysis of the heart rate variability in animals.…”
Section: )mentioning
confidence: 81%
“…The spectral analysis showed an increase in the relative power of low frequencies and a decrease in the relative power of high frequencies of the RRI spectrum. The ranges for LF and HF we used have been validated for the analysis of autonomic influences in heart rate variability in fetal sheep by Kimura et al (21). Although these authors used cycles/beat in their analysis, the frequency ranges for LF and HF are equivalent when expressed in Hertz.…”
Section: Discussionmentioning
confidence: 99%
“…Power spectral analysis of RRI variability was performed on data from the same file used for the sequence method using fast-Fourier transform and the data integrated over a specified frequency range. The frequency ranges used have been validated for the fetal sheep to represent sympathetic and parasympathetic cardiac modulation (LF, 0.025-0.31 Hz; HF, 0.5-1.25 Hz) (21). Power of RRI spectra in the LF (LF RRI) and HF (HFRRI) range were calculated in normalized units, and the ratio of LFRRI/HFRRI was used as an estimation of sympathovagal balance (31).…”
Section: Animal Studiesmentioning
confidence: 99%